PELATIHAN TAHFIDZ AL- QUR’AN MENGGUNAKAN METODE TASMI’ DAN MURAJA’AH MELALUI PROGRAM KAMPUS MENGAJAR DI KOTA PADANG - Azizah, Dinda Dwi; Kustati, Martin; Amelia, Rezki; Azzahra, Fatimah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This training aims to improve students' memorization of the Al-Qur'an at SD Negeri 08 Pulau Air. Students have difficulty in reading and writing. This problem is caused by a lack of parental assistance in the child's learning process at home and a lack of interest in learning. However, despite these limitations, students have advantages in religious knowledge, such as reading and memorizing the Al-Qur'an juz 30. This Al-Qur'an tahfidz training activity uses the tasmi' and muraja'ah methods with a Service-Learning approach. The implementation of the activity involved 6 students who had the ability to memorize the Al-Qur'an, read makhorijul letters, and apply the rules of tajwid properly and correctly. The training was carried out in 8 meetings in stages. The first stage carried out is the planning stage, at this stage the server carries out observations, needs analysis and activity planning. The second implementation stage is for the service provider to coordinate with the school principal and teachers and conduct tests on students who have the ability to memorize the Al-Qur'an, then carry out activities and deepen the material using tasmi' and muraja'. ah method in accordance with the activity plan. The third closing stage, at this stage there will be practice memorizing and continuing verses, as well as demonstrating students' abilities. The results of this training based on data obtained by researchers and developments obtained by participants show that this training can improve students' memorization abilities and quality at a very good level.